Surveying Medical Mask Waste Generation in Can Tho University, Vietnam - Giao , Nguyen Thanh; Y, Nguyen Nhu; Vy, Pham Ngoc Phuong (Indonesian Journal of Environmental Management and Sustainability, 2023)
Medical mask waste is generated more and more and causes many negative impacts on the environment and human health. This study was conducted to survey the current status of using and managing medical mask waste by students at Can Tho University, Vietnam. The study conducted by direct interviews with 120 students and field observations of the research area. As a result, students of Can Tho University use about 43,850 masks resulting in 153.475 kg of medical mask waste per day. Medical mask waste was not well classified by students. Understandings of students regarding toxicity and non-biodegradable characteristics of medical masks are relatively high. However, the level of awareness of students about medical mask waste has some limitations, through the way that medical masks are considered as household waste and are not really necessary to pay attention to the classification of medical masks. As can be seen that training on waste classification and associated waste containers are urgently needed for better solid waste management in the university. This research will contribute to enriching scientific data sources in the field of solid waste, especially medical mask waste.